Seychelles : First Review under the Extended Fund Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for the Seychelles. (IMF Staff Country Reports; Country Report ;, 2022)
The expected macroeconomic recovery has materialized. Seychelles remains a leader in vaccine coverage at home, and the widespread availability of vaccines in Seychelles' key tourist markets, particularly Europe, is contributing to a strong rebound in tourism. The economic outlook, while positive, remains subject to the uncertain evolution of the COVID-19 pandemic globally.